Association between High Serum Uric Acid Level and Good Outcome in patients of Ischemic Stroke - Maria Wajid, Rabia Rathore, Nasir Farooq Butt, Adil Iqbal, Hina Alatif, Madiha Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the relationship of raised levels of uric acid and good prognosis in patients presenting with acute onset ischemic stroke Study design: A cross-sectional descriptive study. Place & duration of study: The research was done at Medical Emergency, Departments of Neurology and Medicine Mayo Hospital Lahore from April, 2019 to March 2020. Methods: Total 230 patients fulfilling selection criteria were enrolled. Serum uric acid levels were measured at the time of admission. The technique used to assemble data was consecutive non-probability convenience sampling. Patients were divided into two groups Group A (115 patients - having uric acid more than or equal to 7 mg/dl) and Group B (115 patients - having uric acid less than 7 mg/dl). After 5 days, Modified Rankin score (mRS) was noted and link between raised uric acid levels and mRS was determined. Results: Total 230 (115 Group A/ 115 Group B) patients were selected for this study. Among Group A, mean age was 57.2±10.4 years and 58.8±10.1 years among Group B. Among Group A, there were 72(62.6%) males and 43(37.4%) females, while 79(68.7%) males and 36(31.3%) females among Group B . By comparing good outcome between groups, it was found that percentage of good outcome was 42.6% with high uric acid level and 16.5% with normal uric acid level. The difference was significant (p=0.00001) and with odds ratio as 3.751. Conclusion: There is an association between high serum uric acid level and good outcome in patients presenting with stroke. Patients with high serum uric acid level have significant chances to have good outcome. Keywords: Serum Uric Acid, Acute Ischemic Stroke, modified Rankin Score